Distribution of mass of the protoplanetary disk HL Tau - Buitrago Carreño, Nidia Yiseth; Poveda Tejada, Nicanor; Vera Villamizar, Nelson (TECCIENCIA, 2016)
A recent image of ALMA, of the protoplanetary disk around the star HL Tau, shows that the disc consists of several bright concentric rings separated by gaps. There is a hypothesis that these gaps are due to the presence of planets, but there are some difficulties with this interpretation: The planets are too close, generating orbital instability and should not exist planetary formation processes so advanced because the star is too young. This paper shows that the gaps are an effect of the distribution of matter of the disk. In most models assume that the disc consists of a continuous distribution of materia and gas, however, by orbital resonance effect, the disc has an internal structure: It is a superposition of distribution functions that give rise to the characteristic shape of the disc. The mass distribution is obtained, and a preliminary study of the orbits is done, finding that they are stable.